Extend Differential Transform Methods for Solving Differential Equations with Multiple Delay - Mohammed, Gh. J.; Fadhel, F.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we present an approximate analytical and numerical solutions for the differential equations with multiple delay using the extend differential transform method (DTM). This method is used to solve many linear and non linear problems.